Validity and reliability of the Smart Groin Trainer for measuring hip adduction strength - Sousa, A. C.; Marques, D. L.; Calado, A. M.; Pacheco, C.; Marinho, D. A.; Marques, M. C.; Travassos, B. F. (Journal of Human Kinetics, 2022)
We analyzed the Smart Groin Trainer device's validity and reliability to measure the isometric hip adduction strength during the adductor squeeze strength test. Fifteen professional soccer players (25.33±4.06 years) and fifteen university students (21.60±1.76 years) participated in this study. All participants performed the squeeze strength test using two portable dynamometers: Smart Groin Trainer and Globus Ergometer. Three maximal isometric hip adduction contractions lasting 5s, interspersed by 3min rest intervals, were performed. Reliability was analyzed with intraclass correlation coefficients, standard error of measurements, and minimal detectable change. The absolute percent error and inter-device accuracy were also analyzed. Correlation analysis assessed the inter-device concurrent validity. The results found no significant differences (p>0.05) between devices in the squeeze strength test values in soccer players and university students. Inter-device comparisons revealed excellent levels of reliability and accuracy in soccer players. Concurrent validity measures revealed strong inter-device relationships in soccer players (r=0.89) and very strong relationships in university students (r=0.99). Intra-device analysis using the Smart Groin Trainer showed excellent relative and absolute reliability in tested soccer players. Our data demonstrated excellent levels of agreement between both dynamometers during the squeeze strength test, suggesting the Smart Groin Trainer as a valid, reliable, and accurate device to measure isometric hip adduction strength